Riau Badminton Center Di Pekanbaru Dengan Pendekatan Arsitektur Hijau - Teguh Asrin; Wahyu Hidayat; Muhammad Rijal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Badminton is a popular sport in the world, especially East Asia and Southeast Asia. The game of badminton is a very common thing for Indonesian people, because in almost every region of Indonesia badminton game into sports interests of society. Riau Badminton Center is building a sports stadium badminton equipped with supporting facilities such as dormitories. Existence Riau Badminton Center is expected to accommodate young athletes, especially in the city of Pekanbaru so as to berbucara least the national arena. In designing this building, green architecture approach is used to address a variety of issues related to climate conditions that affect the site. Some Green Architecture principles applied in the design, such as: (1) The energy savings such as natural lighting; (2) Optimizing the use of natural energy such as the use of solar panels; (3) Percentage of green spaces; and (4) responsive to environmental conditions. The building will be designed with a green architectural approach that will make the building more to implementing environmentally friendly elements and response to climate. Riau sports facilities building Badminton Center uses the concept of Dynamic Transformation in its design. Concepts and themes will also be tailored to the needs.Keyword: Riau Badminton, Center, Green Architecture, Dynamic Transformation.